Direct gas-phase formation of complex core–shell and three-layer Mn–Bi nanoparticles. Issue 95 (27th September 2016) - Mukherjee, P.; Balamurugan, B.; Shield, J. E.; Sellmyer, D. J.
Abstract : STEM images and elemental maps of Mn and Bi showing formation of complex core–shell and three-layer structure. Abstract : We report the formation of complex core–shell and three-layer Mn–Bi nanoparticles in a single step inert-gas condensation process. These structures have been achieved by controlling the thermal environment of the nanoparticles. High resolution transmission electron microscopy, high-angle annular dark-field imaging in scanning transmission electron microscopy mode, and elemental mapping by energy dispersive spectroscopy have been used to determine the crystal structure and chemical composition of the nanoparticles. These particles exist in two forms: (1) a crystalline Bi core with an amorphous Mn-rich shell, and (2) a crystalline Bi annular shell between two amorphous layers with high Mn concentration. These particles show significant magnetic hysteresis possibly arising from the change in bond length between Mn atoms introduced by Bi atoms in the bonding environment of the Mn atoms.